Donne a processo per apostasia nell’Archivio Diocesano di Napoli: materiale inedito. - Mazza, Anna (Scripta, 2022)
The study of unpublished archival material concerning trials for apostasy against women, offers the possibility of building new research perspectives around «marginal» categories starting from a real narrative, without filters, and in some cases, as for Caterina and Margarita, through the very voice of the protagonists. In this succession of questions and answers that are reported in the dossier of the trial of the Holy Office, the human events of two women unravel that we will not find in the writings or verses of poets but are real witnesses of their time and become flesh and voice through a process. Remembering them is certainly an act of justice